Expression of bcl-2 in bladder neoplasms is a cell lineage associated and p53-independent event. Issue 1 (February 1997) - Lu, Q L; Laniado, M; Abel, P D; Stamp, G W; Lalani, E N
Abstract : AIMS: To investigate bcl-2 and p53 protein expression in hyperplastic, metaplastic and neoplastic epithelia of the urinary bladder in relation to cell lineages (transitional versus glandular epithelia). METHODS: Formalin fixed, paraffin wax embedded archival tissue blocks of 29 transitional cell carcinomas (TCC), 11 adenocarcinomas, five specimens of cystitis glandularis, four papillomas, and seven samples of morphologically normal bladder mucosa were examined immunohistochemically with antibodies specific to bcl-2 and p53. Consecutive sections were used to assess co-expression of the two proteins. RESULTS: bcl-2 protein was expressed heterogeneously in basal cells of the normal transitional epithelium, whereas p53 was rarely detectable in either normal or hyperplastic epithelium. Of the 29 TCCs, 20 (69%) expressed immunodetectable p53 which was positively associated with grade. In contrast, bcl-2 was detected in four (14%) TCCs and its expression was not associated with grade. bcl-2 was expressed constitutively in all five specimens of cystitis glandularis and in all adenocarcinomas; p53 was co-expressed in most of the latter. There was no association between bcl-2 and p53 protein expression in the TCCs. Expression of bcl-2 protein correlated negatively with grade of adenocarcinoma. CONCLUSION: In bladder adenocarcinomas, bcl-2 expression correlated negatively with tumour grade whereas p53 was associated positively with tumour grade. The association of bcl-2 with cystitis glandularis and adenocarcinoma but not TCC suggests that it may be involved in triggering a lineage switch converting transitional epithelium to a glandular phenotype.